Networks and Communications (NetCom2013) Proceedings of the Fifth International Conference on Networks & Communications - Meghanathan, Natarajan; Nagamalai, Dhinaharan; Rajasekaran, Sanguthevar (Lecture Notes in Electrical Engineering,, 2014)
This book covers theory, methodology and applications of computer networks, network protocols and wireless networks, data communication technologies, and network security. The book is based on the proceedings from the Fifth International Conference on Networks & Communications (NetCom). The proceedings will feature peer-reviewed papers that illustrate research results, projects, surveys and industrial experiences that describe significant advances in the diverse areas of computer networks & communications.